Qualidade dos ovos frescos e armazenados de poedeiras semipesadas alimentadas com semente residual de urucum - Tavares, Thaís Cruz Lopes (2015)
This study was conducted in order to verify the effects of the inclusion of annatto residual seed (SRU) in the feed of laying hens red eggs on the quality of the fresh egg depending on the storage time to 6 ° C for up to 30 days. The experimental design was completely randomized in a factorial 3 x 6 (six experimental diets and three storage times), six replicates per treatment, totaling 108 observations. Initially, 288 laying hens Lohmann Brown at 34 weeks of age were randomly distributed, totaling 48 birds (6 repetitions of 8 birds) for each experimental diet, which consisted of T1 - ration composed based on corn and soybean meal (positive control); T2 - diet containing sorghum in total replacement of corn without the addition of pigmentante (negative control); T3, T4, T5 and T6 - feed containing sorghum in total replacement of corn, with the addition of 2.5; 4.5; 6.5 and 8.5% residual annatto seed (SRU), respectively. In the 10th week, after the start of the experimental supply feed were collected 6 eggs of each repetition for evaluations on day 0 and after 15 and 30 days of storage. We evaluated the albumen quality parameters (Haugh units, percentage, pH, formation and foam stability), gem (percentage and pH, subjective and objective color and lipid oxidation) and bark (percentage and specific gravity). There was a significant interaction between the experimental feed and the storage time, only for yolk color variables. However, the addition SRU linearly increases the perception of color by colorimetric range, reduced lightness (L *), increased redness (a *) and yellow (b *), while increasing storage time increased perception of color by colorimetric range, intensity of yellow (b *) and reduced lightness (L *) and redness (a *). The experimental feed does not influence other gem quality variables, but the storage time caused a loss in the quality of albumen and shell, except the percentage of shell and albumen pH. It is possible to include up to 8.5% of SRU in feed containing sorghum for laying red eggs without harming the quality of the albumen and yolk of fresh and stored eggs, and improve the color of the yolk with the inclusion from 2.5 %.